Avaliação do parâmetro de propagação de sedimentos do modelo de Williams (1975) na bacia do rio Vacacaí-Mirim com o auxílio de técnicas de geoprocessamento - Casagrande, Leandro (2004)
The objective of this study was to determine sediment yields in the Vacacaí-Mirim watershed which has an area of some 1150 km2, and which lies between 29°36′55″ to 29°39′50″S and 53°46′30″ to 53°49′29″W. Estimates were made using the Modified Universal Soil Lost Equation (MUSLE) in conjunction with the Williams (1975) sediment routing model. The catchment was divided into 93 sub-basins, with drainage areas ranging from 0.7 to 115 km2. The MUSLE parameters were determined in the 93 sub-basins; three sub-basins, representative of the three physiographic provinces in the catchment, were selected for the determination of William s routing coefficient (B). Requisite data were obtained from a combination of sources (e.g. satellite imagery; national army maps) and entered into a GIS database. The Soil Conservation Service curve number methodology and the Santa Maria rainfall equations developed by Belinazo & Paiva (1991) were used to generate hydrographs for the study area. The methodology permess the obtention of William s routing coefficient for each one of the provinces in the catchment, the sediment routing was 299,42 t/km2/year.